Ion energy and ion angular distributions in RF capacitively coupled plasma sources: pure argon and argon-oxygen mixtures - Manuilenko, O.V.; Minaeva, K.M.; Golota, V.I. (Вопросы атомной науки и техники, 2006)
Single and dual frequency capacitively coupled plasma (CCP) sources operating in pure Ar, O₂ and Ar/O₂ mixtures are investigated by means of particle-in-cell/Monte Carlo collisions (PIC/MCC) simulations. The different possibilities to control ion energy distribution functions (IEDFs) and ion angular distribution functions (IADFs) on electrodes are found. It is shown that the driven voltage and frequency in single frequency capacitive discharges are control the IEDFs on the electrodes. It is demonstrated that the low frequency voltage in dual frequency CCP sources controls the IEDFs and IADFs. It is shown that the IEDFs on electrodes can be controlled by Ar/O₂ ratio.